Eyelid-associated complications after autogenous fat injection for cosmetic forehead augmentation - Paik, Ji-Sun (BioMed Central, 2013)
BACKGROUND: We report two cases of unilateral upper eyelid swelling with multiple small lumps as an unusual complication of autogenous fat injection for cosmetic forehead augmentation. CASE PRESENTATION: Two female patients were referred to our clinic for unusual unilateral eyelid swelling, with multiple small lumps. The duration of symptoms differed in each case, but both patients had a history of autogenous fat injection for cosmetic forehead augmentation at a local plastic surgery clinic. The lumps were small (diameter 5 mm~10 mm), palpable, hard, and nonmobile, and were evaluated by magnetic resonance imaging (MRI). Lumps from the eyelids of two patients were excised under general anesthesia. All of the masses were located deeply and found near the superior orbital rim or lateral orbital rim. The lumps exhibited chronic inflammation with fibrosis. Some of the lumps showed foamy histiocytic aggregation and foreign body lipogranuloma, resulting from iatrogenic fat injection. After excision, all masses and swelling disappeared, and moderate ptotic eyelid or lagophthalmos of affected eyes also improved. CONCLUSIONS: To our knowledge, eyelid swelling with multiple lumps in the eyelid is a very rare complication of autogenous fat injection for cosmetic forehead augmentation. This report should be helpful for ophthalmic clinicians who encounter these unusual symptoms.